2023
DOI: 10.1200/jco.2023.41.4_suppl.183
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phosphocreatine (PC) as a predictive biomarker for immune checkpoint inhibition in patients with refractory metastatic colorectal cancer (mCRC): Analysis of the CCTG CO.26 trial.

Abstract: 183 Background: In response to energetic stress, colorectal cancer cells secrete creatine kinase brain-type (CKB). CKB converts creatine and ATP from the extracellular matrix to PC, which is imported intracellularly to sustain survival and metastatic spread. In addition, PC modulates immune cell functions and may play a role in mediating responses to immune checkpoint inhibition. CO.26 was a phase II trial (NCT02870920) that randomized patients (pts) with refractory mCRC to durvalumab plus tremelimumab (D+T) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is supported by a study into the pharmacokinetics of exogenous phosphocreatine, which previously demonstrated that all of the pre-dose plasma samples had phosphocreatine concentrations below the limit of quantitation of 1.96 µmol/L (He et al 2020 ). Plasma phosphocreatine concentrations of the same order of magnitude were found in metastatic colorectal cancer patients (Ma et al 2023 ). Furthermore, non-clinical pharmacokinetic study demonstrated that nearly three fourth of an intravenously administrated phosphocreatine dose was quickly converted into creatine (Xu et al 2014 ).…”
Section: Discussionmentioning
confidence: 72%
“…This is supported by a study into the pharmacokinetics of exogenous phosphocreatine, which previously demonstrated that all of the pre-dose plasma samples had phosphocreatine concentrations below the limit of quantitation of 1.96 µmol/L (He et al 2020 ). Plasma phosphocreatine concentrations of the same order of magnitude were found in metastatic colorectal cancer patients (Ma et al 2023 ). Furthermore, non-clinical pharmacokinetic study demonstrated that nearly three fourth of an intravenously administrated phosphocreatine dose was quickly converted into creatine (Xu et al 2014 ).…”
Section: Discussionmentioning
confidence: 72%